What types of citizens require opportunities for interactions with people in the local community? A quantitative study - Shimizu, Yuho; Kudo, Yasuyuki; Igeta, Yuki; Fukuyama, Shuhei; Tomabechi, Tobu; Ohtaka, Mizuka; Hashimoto, Takaaki; Karasawa, Kaori (Frontiers in Social Psychology, 2025)
There are examples of governments and companies providing citizens with opportunities to interact with people in local communities. This study aimed to examine the individuals who should be provided with opportunities to interact with others in a community. We tested four hypotheses: people with greater sense of community (H1) and need to belong (H2) will have more need for provided opportunities for interaction, and people with greater sense of community (H3) and need to belong (H4) will have more positive interaction expectancy (i.e., prediction of self-perceptions improved through provided opportunities for interaction with people in the local community). By examining this outcome variable, we can better assess the potential impact of government- or company-led initiatives that provide opportunities for interaction on improving citizens' wellbeing. We conducted two online surveys with Japanese adults. The results showed that in both Studies 1 and 2 (N = 980 and 983, respectively), participants with a higher sense of community and need to belong were more likely to desire opportunities provided to interact with people in local communities (supporting H1 and H2). In addition, Study 2 showed that participants with a higher sense of community and a need to belong believed that such provided interaction opportunities would make them hold more positive self-perceptions (supporting H3 and H4). Additionally, in both surveys, individuals with more negative self-perceptions in interpersonal relationships had a lower need to belong. This study suggests the importance of considering people's views toward opportunities for intra-community interaction, and provides preliminary data contributing to the discussion of whether and how such opportunities should be implemented in local communities.